Racism Reflected In Maya Angelou's Poems - Ilham, Ria Resky Hardianti; , Dr. M. Thoyibi, M.S; , Dr. Phil. Dewi Candraningrum, M.Ed (2015)
The major problem of this research is racism reflected in Maya Angelou's poems. The aims of this research is to find out how racism reflected in Maya Angelou's poems, to explain types of racism in Maya Angelou's poems, and to find out why racism become the important issue in Maya Angelou's poems. This research focuses in Maya Angelou's poem especially about racism. The type of the research is qualitative research. The method of data collection is document analysis, and the technique of data collection is note taking, while the technique of data analysis is descriptive analysis in which the researcher interprets the text and the content relating to the psychological of the major character. This research uses two data sources, namely primary and secondary data source. The primary data source of the study is Maya Angelou's poem itself, from the collection of Maya Angelou published in 1994. The secondary data sources are Biography of the author Maya Angelou, websites in the internet about Maya Angelou, and other resources which support to analyze. Based on structural analysis and the psychological approach, the researcher concludes that Maya Angelou's poems reflected racism based on the poem text and the expression in the poem. The expressions here are dictions which divide into four such as dialect and accent, special expression, special term and borrowing. Imagery and symbol also two expressions supported Maya Angelou's poem to reflect racism in visual and auditory imagery, also symbolize the particular words in the title of the poem. Maya Angelou's poems also indicate types of racism such as slavery, discrimination, segregation, Hegemony, prejudice and stereotypes and class struggle. The last conclusion is Maya Angelou choose racism as the important issue in her poems because she is an African-American poet and activist.